Revolting Against Imperialism and Capitalism in Sherlock Holmes: a Game of Shadows (2011) - Adji, Alberta Natasia (Humaniora, 2017)
The purpose of the study was to reveal the struggle among imperialism, capitalism, and social class dominance found within Guy Ritchie’s A Game of Shadows (2011), which was set in Britain, France, and Germany in 1891. British imperialism, capitalism, and social class were very well-related since they formed the basic classic social tradition in European countries that confined minorities such as working-class people and immigrants. The study was particularly focused on (1) the imperialist and capitalist representations were portrayed by Professor Moriarty as the much honoured academic figure who was able to disguise his criminal activities, and (2) the revolt of the marginalized people which were represented by the working-class; Gypsy immigrant minorities who are isolated from the imperialist West European social class strata. The study was conducted using the perspectives of AJ Greimas’ narrative structure through identifying all of the sequences and actantial models of the film, as well as relating them to capitalism and social class issues. The result of the study shows that the film has managed to show the success in fighting against imperialism and capitalism that initially determine the characters’ positions.